Optimization of Sustainable Development Based on Triple Bottom Line Theory - Roki' Khairullah; Mohammad Sodik; Hartini Prasetyaning Pawestri (Optima Science, 2024)
This research aims to analyze the implementation of Green Accounting based on Triple Bottom Line Theory in supporting Sustainable Development in the Bumdes